Dampak Keberadaan Tambang Nikel PT JAM Terhadap Lingkungan Sosial Masyarakat - Moh. Dahlan; Surdin Surdin; Sitti Kasmiati (Jurnal Penelitian Pendidikan Geografi, 2025)
The existence of the PT JAM nickel mine certainly brings significant changes to the surrounding area. The changes felt by the community certainly have positive and negative impacts on the community's social environment. This research aims to determine the impact of the existence of the PT JAM nickel mine on the social environment of the Molore Village community. The method used in this research is descriptive qualitative. The research results show that PT JAM's nickel mining activities have positive and negative impacts on the social environment of the community, especially the fields of education, health and community economy. Positive impact in the education sector, namely the distribution of goods and services to improve the quality of education. In public health, it is a health examination service and advice and guidance on public health which is carried out 3 times a year. In the economic sector, the community is a source of livelihood for the community, increasing income and opening up new job opportunities for the community. Negative impact in the field of education is promiscuity with adults carried out by students, such as smoking, drinking and drug cases. In terms of public health, air pollution due to PT JAM's nickel mining activities can disrupt people's respiratory tract. In the economy, there is an economic gap between communities.